Global Sustainability Competitiveness of the Member States of the Organization of Turkic States Evaluating Their Performance With Integrated MEREC-MABAC Methods - Kara, Mehmet Akif (Fırat University, 2025)
Sustainability and competition is a concept that directly concerns individuals and organizations in both micro and macro terms. Countries produce and implement policies for sustainable competition in order to keep their social, economic, political and social welfare levels at a high level. The Global Sustainable Competitiveness Index is an index that determines the level of countries in 196 indicators and 6 basic indices and constitutes the basis for strategic policy making. In this study, the global sustainability competitive performance of the member countries of the Organization of Turkic States is evaluated. In the study, 7 alternatives were evaluated based on 6 criteria. The weighting of the criteria was made with the MEREC method and the “natural capital” criterion was found to be the criterion with the highest weight. As a result of the analysis made with the integrated MEREC-MABAC methods, Hungary has the highest performance. The lowest country was Turkmenistan. With the same data set, the rankings were also performed with MOORA and OCRA methods and the results were compared with Spearman Correlation analysis. There is a statistically close to perfect relationship between the methods. When compared with the index results, there is no difference. Sensitivity analysis reveals that the results are reliable

Sürdürülebilirlik ve rekabet hem mikro hem de makro anlamda birey ve kurumları doğrudan ilgilendiren bir kavramdır. Ülkeler de sosyal, ekonomik, politik ve toplumsal olarak refah seviyelerini üst düzeyde tutmak için sürdürülebilir rekabet için politika üretmekte ve uygulamaktadır. Küresel Sürdürülebilir Rekabet Endeksi, ülkeleri 196 gösterge ve 6 temel endekste düzeylerini belirleyen ve stratejik politika üretmeleri bağlamında temel teşkil eden bir endekstir. Bu çalışmada Türk Devletleri Teşkilatı üyesi ülkelerin küresel sürdürülebilirlik rekabet performanslarının değerlendirilmektedir. Çalışmada 7 alternatif 6 kriter üzerinden değerlendirmiştir. Kriterlerin ağırlıklandırılması MEREC yöntemi ile yapılmış ve “doğal sermaye” kriteri ağırlığı en yüksek kriter olarak bulunmuştur. Bütünleşik MEREC-MABAC yöntemleriyle yapılan analiz sonucunda performansı en yüksek ülke Macaristan olmuştur. En düşük ülke ise Türkmenistan olmuştur. Aynı veri seti ile sıralamalar ayrıca MOORA ve OCRA yöntemleriyle gerçekleştirilmiş ve sonuçlar Spearman Korelasyon analizi ile karşılaştırılmıştır. Yöntemler arasında istatistiksel olarak mükemmele yakın bir ilişki vardır. Endeks sonuçları ile karşılaştırıldığın da farklılık olmadığı görülmektedir. Yapılan duyarlılık analizi ile sonuçların güvenilir olduğu ortaya koyulmaktadır
Türk Devletleri Teşkilatı Üyesi Ülkelerin Küresel Sürdürülebilirlik Rekabet Performanslarının Bütünleşik MEREC-MABAC Yöntemleriyle Değerlendirilmesi
Keywords: Decision Support and Group Support Systems; Karar Desteği ve Grup Destek Sistemleri; Information Systems For Sustainable Development and The Public Good; Sürdürülebilir Kalkınma ve Kamu Yararına Bilgi Sistemleri